FORTIFIED SETTLEMENTS OF THE BASIN OF THE RIVER CHEPTSA: FEATURES OF THE DEVELOPMENT AND USE OF THE SITES - Ivanova, M.G.; Zhurbin, I.V. (Perm Federal Research Centre Journal, 2017)
The article presents the results of the study of the settlements of the basin of the River Cheptsa, using natural scientific methods, which provided fundamentally new sources about the structure and stages of the development of the sites. A significant result of the research is the discovery of structural parts of the defense lines of fortifications at major settlements. For the first time the complex structure of an ancient settlement was studied in Idnakar settlement (the beginning of the IX-XIII centuries), the largest site of the Finno-Ugric Middle Ages, which developed through the expansion of inhabited areas, by fencing a new defense line and strengthening the fortification possibilities. In 2011-2016 new materials were received about the structure and planning of the site of Uchkakar, a synchronous Kushmansky ancient settlement. The entire area was studied with the help of geophysical methods with the localization of facilities planning (buildings, storage-pits, hearths) and an internal line, separating the cape area, that cannot be fixed at present was found. The key areas, where archaeological excavations took place, were chosen in order to establish the nature of the objects identified by geophysical methods and obtain materials for chronological definitions. The obtained materials showed that the ancient settlement functioned within the X-XIII centuries. It has been revealed that the external part was populated later than the internal and middle ones, most likely in the XI century. The territory outside the external line of fortifications was settled approximately at the same time. The initial period of the development of the site remains not clear, however, it is logical to suppose that it was settled a bit earlier than the middle one. In general, direct analogies to the dynamics of the development of the Idnakar settlement structure can be traced. But the identification of the developed part outside the outer fortifications in Uchkakar opens prospects for further research to elaborate on the peculiarities of the development and use of the sites.